Análise da oferta de alho em Minas Gerais em 1948-70 - Brun Rojas, Marciano; Teixeira Filho, Antônio Raphael; A Penna, Julio; Barbosa, Túlio (Revista Ceres, 2025)
Despite the economic importance of garlic in Brazil, a considerable amount must be imported to satisfy national demand. For the last five years Brazil has been importing about 28 percent of the garlic consumed Minas Gerais is an important garlic producing state.